Night-shift work and hematological cancers: a population based case-control study in three Nordic countries - Madar Talibov; Eero Pukkala; Jan Ivar Martinsen; Laufey Tryggvadottir; Elisabete Weiderpass; Johnni Hansen (Nordic Association of Occupational Safety and Health (NOROSH), 2018)
OBJECTIVE: The aim of this case-control study was to assess the effect of night-shift work on the risk of hematological cancers. METHODS: The study included 39 371 leukemia, 56 713 non-Hodgkin lymphoma, 9322 Hodgkin lymphoma, and 26 188 multiple myeloma cases diagnosed between 1961 and 2005 in Finland, Sweden, and Iceland. Five controls for each case were selected from the Nordic Occupational Cancer Study (NOCCA) cohort, matched by year of birth, sex and country. Night-shift exposure was assessed by using the NOCCA job-exposure matrix (JEM). Odds ratios (OR) and 95% confidence intervals (95% CI) were calculated from conditional logistic regression models. RESULTS: Overall, night work was not associated with a risk of hematological cancers. We observed a small but non-significantly increased risk for leukemia (OR 1.07, 95% CI 0.99-1.16), especially for acute myeloid leukemia (OR 1.15, 95% CI 0.97-1.36) among workers exposed to a high level of cumulative night work exposure. Night work exposure was not associated with lymphatic cancers and multiple myeloma. CONCLUSION: This study did not support associations between night-shift work and hematological cancers.